2017
DOI: 10.1039/c6mb00842a
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of lipids is central to replicative senescence

Abstract: Cellular replicative senescence, a state of permanent cell-cycle arrest, has been linked to organismal aging, tissue repair and tumorigenesis. In this study, we comparatively investigated the global lipid profiles and mRNA content of proliferating and senescent-state BJ fibroblasts. We found that both expression levels of lipid-regulating genes and the abundance of specific lipid families, are actively regulated. We further found that 19 specific polyunsaturated triacylglycerol species constituted the most pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
78
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 73 publications
(82 citation statements)
references
References 61 publications
4
78
0
Order By: Relevance
“…We followed similar lipidomics workflow as how we described in the past for sample preparation, data acquisition, and analysis. [ 8,11,20 ] Briefly, five biological replicates of proliferating and senescent cells were analyzed in positive and negative electrospray ionization modes. Peak alignment based on mass‐to‐charge ratio ( m / z ), grouping of different adducts, retention time, and isotopic ratio was carried out in Profinder (Agilent Technologies).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We followed similar lipidomics workflow as how we described in the past for sample preparation, data acquisition, and analysis. [ 8,11,20 ] Briefly, five biological replicates of proliferating and senescent cells were analyzed in positive and negative electrospray ionization modes. Peak alignment based on mass‐to‐charge ratio ( m / z ), grouping of different adducts, retention time, and isotopic ratio was carried out in Profinder (Agilent Technologies).…”
Section: Resultsmentioning
confidence: 99%
“…LC‐MS analysis was performed as described previously. [ 8,11,20 ] Briefly, LC‐MS data acquisition was performed using an Agilent 1260 HPLC paired with an Agilent 6530 Accurate‐Mass Quadrupole Time‐of‐Flight mass spectrometer (Agilent Technologies, Santa Clara, CA). Prior to analysis, separation was achieved with reverse phase chromatography.…”
Section: Methodsmentioning
confidence: 99%
“…As accumulation of triacylglycerol (TG) is central to replicative senescence (33), we also performed senescence-associated(SA)- b-Gal staining on all six groups [Control, Tg(Wnt), Tg(Myc), Tg(Kras), Tg(Wnt&Kras), Tg(Myc&Kras)], and found that Tg(Kras), but not Tg(Wnt) or Tg(Myc), induced notable cell senescence in the liver; senescence was significantly alleviated in Tg(Wnt&Kras) and Tg(Myc&Kras) ( Fig. 3C; Supplementary Fig.…”
Section: Wnt/myc Activity Represses the Extensive Hepatic Steatosis Amentioning
confidence: 99%
“…4) (42,79,80,117). As first observed using microarrays, CD36 mRNA expression is induced in senescent cells as member of a number of lipid-regulating genes possibly leading to accumulation of ceramides and triacylglycerols with long and very long unsaturated fatty acyl side chains (259,260). Recent studies suggest that during senescence, CD36 up-regulation is an important event in initiating the SASP, in activating of the Src/p38/NFκB pathway and of lysosomal senescence-associated β-galactosidase expression in response to senescent stimuli such as βA (259,261).…”
Section: Modulation Of Signaling Pathways By Vitamin E Relevant To Cementioning
confidence: 83%